Measuring transformative virtual reality experiences in children's drawings. - van Limpt-Broers, H. Anna T.; Postma, Marie; Louwerse, Max M. (Memory & Cognition, 2025)
Transformative experiences in an individual's life have a lasting impact on identity, belief system, and values. At the core of these experiences is the complex emotion of awe that promotes learning, making it worthwhile to study from an educational point of view. Drawing studies may provide a useful measure of awe in children—one that is more intuitive and attractive than questionnaires alone. Previous studies conducted with adults indicated that the diminished self, associated with transformative experiences, manifests in an actual decrease in size for figures representing the self in drawings. In the current study, self-representation was investigated in drawings of 10- to 12-year-old primary school children within the context of an immersive virtual reality (VR) experience that elicits the overview effect, known to lead to an intense apperception of awe. We did not replicate the adult findings regarding self-size in this younger age group. However, details and complexity in children's drawings appeared to be impacted by the awe-elicitation procedure in VR. These elements subsequently correlated to learning gains instead of the overview effect, indicating that this measure could be linked to cognitive ability. The findings of the current study contribute to a better understanding of how drawings reflect self-transcendental experiences; however, they also reveal that in younger age groups, they are not necessarily reflected in decreased self-size.